Risk and resilience among young adults experiencing homelessness: A typology for service planning. (February 2018) - Narendorf, Sarah Carter; Bowen, Elizabeth; Santa Maria, Diane; Thibaudeau, Eva
Abstract: Purpose: This study examined risk and resilience indicators in a sample of young adults experiencing homelessness to identify subgroups with different service needs. Methods: Data came from a 2014 survey of homeless young adults (age 18–24) in Houston ( n  = 374). Participants self-reported risk and resilience indicators which were used to fit a latent class model. Results: A four-class solution was the best fit. Group-1 ( n  = 73), had high adult support and low trauma. Group-2 ( n  = 60) had low trauma but low adult support. Group-3 ( n  = 151), had high trauma exposure, high rates of mental health problems and low substance use. Group-4 ( n  = 90), had high rates across all risk variables. Conclusion: Trauma, adult support, and substance use were key distinguishing features to inform screening and service planning. Highlights: Four subgroups of homeless young adults were identified with different service needs. Exposure to childhood trauma characterized groups with higher needs. The highest need group had mental health, substance use, and criminal justice problems. Screening tools can identify these factors to distinguish subgroups. Each group suggests different service needs at varying levels of intensity.